An Improved Form of Hazen-Williams Equation for Pressurized Flow - Darweesh, Moustafa S.; Salah, Wael A.; Awwad, Tarek M.; Ragab, Ehab M.; Ahmed, Anwar A. (Engineering, Technology & Applied Science Research, 2024)
This study performed a sensitivity analysis to correlate the frictional head loss calculated by the Darcy-Weisbach (D-W) and the Hazen-Williams (H-W) formulas. For a broad variety of fluid temperatures, velocities, and pipeline diameters, this study considered an extensive discussion and analysis to determine friction loss within pressurized pipelines using Microsoft Excel. Regression analysis and statistical tools were applied to improve the relationship between the two equations. A more accurate expression was developed to calculate the friction loss in terms of the H-W equation. The estimated values were compared with previous experimental and numerical studies, and a good agreement was observed. The proposed model was evaluated using WaterGEMS software in an application example of a water supply system against the D-W and H-W equations. Good agreements were recorded between predicted values and previous studies, with an error of less than 1%. These findings can be used to improve the hydraulic design of engineering applications.